The Influence of Material Mastery and Self Efficacy on The Practical Ability of Electronic Ignition Systems - Yuli Ermawati; Bambang Suprianto; Ahmad Imam Agung (Jurnal Pendidikan : Riset dan Konseptual, 2024)
The goal of the research This is to understand how the Department of Vehicle Engineering Light Automotive at SMKN 1 Semen Kediri's mastering material and self-efficacy affect ability practice system ignition electronic students. Examine This was completed using an instrument questionnaire and method survey. 102 students in class XI majoring in TKRO SMKN 1 Semen Kediri make up the research sample. Multiple linear regression analysis was used to examine the collected data. The findings of the study indicate that mastery content and self-efficacy have a favorable and significant impact on students' capacity to utilize the system ignition electronic at SMKN 1 Semen Kediri's TKRO department. In addition, there is a relationship between students' self-efficacy and their mastery of the subject regarding ability practice, indicating that students who possess both of these traits are more practiced in understanding and mastering system ignition electronic. Examine This helps students grasp the aspects that influence their ability to comprehend and manage the electronic ignition system. The results of this research can potentially be used as input by educators and educational institutions to design curriculum and learning initiatives within the TKRO department.